Ekopedagogi Digital Hindu: Integrasi Spiritualitas dan Teknologi untuk Kesadaran Ekologis Berkelanjutan - Pustikayasa, I Made; Saputra, Putu Wisnu; Mertayasa, I Komang (Bawi Ayah: Jurnal Pendidikan Agama dan Budaya Hindu, 2025)
The global ecological crisis threatens the sustainability of life and demands a fundamental transformation in education. This study explores how Hindu ecotheological values can be integrated into digital learning to foster authentic and sustainable ecological awareness. The discontinuity between contemplative spiritual dimensions and concrete ethical practices in digital learning presents a major challenge for contemporary technocratic educational paradigms. Employing a qualitative, concept-based approach with reflective hermeneutics, this research analyzes the esoteric dimensions of Hindu ecotheology through fundamental concepts such as Tat Tvam Asi, Rta, Dharma, and Tri Hita Karana, as well as its exoteric dimensions through ritual practices and environmental ethics. The study integrates Habermas’s lifeworld-system dialectic and Tillich’s symbolic theology as critical analytical frameworks. The proposed conceptual model, Hindu Digital Ecopedagogy, integrates three main components: spiritual ecology, digital pedagogy, and ecological consciousness, using a spiral approach that connects esoteric spiritual experiences with exoteric ecological actions. The research contributes by developing an integrative framework that overcomes the dichotomy between the sacred and secular, and between contemplation and action, in digital learning for sustainability.